2015
DOI: 10.1037/h0101279
|View full text |Cite
|
Sign up to set email alerts
|

Performance of children/adolescents with autism spectrum disorders in executive function: Study of case series.

Abstract: Autism spectrum disorder (ASD) is a developmental condition characterized by various cognitive and behavioral symptoms that may be associated, among other factors, with executive dysfunction. However, the relationship between these aspects still needs to be understood in more detail. The present study investigated associations and dissociations in the performance of 11 children/adolescents who were diagnosed with ASD without mental retardation, aged 10–15 years, in tasks that assessed executive function and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Approximately 41-78% of children diagnosed with an autism spectrum disorder (ASD) also experience documented executive function (EF) deficits. EF skills are a set of mental processes that aid in the areas of attention, problem solving, and self-control (Czermainski et al, 2015).…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 41-78% of children diagnosed with an autism spectrum disorder (ASD) also experience documented executive function (EF) deficits. EF skills are a set of mental processes that aid in the areas of attention, problem solving, and self-control (Czermainski et al, 2015).…”
Section: Autism Spectrum Disordersmentioning
confidence: 99%
“…Research has indicated that there is often a contradiction between the results of formal assessments and functional self-report data by the parent or child (Czermainski et al, 2015). This can be frustrating for individuals and families who experience a child's struggle with EF skills in their day-to-day tasks, while diagnostically they may not be showing significant deficits.…”
Section: From Pagementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it may be pointed out that formal tests possibly lack ecological validity. 29,30 Therefore, experts should also rely on clinical observations in real life.…”
Section: Executive Functionmentioning
confidence: 99%